The effectiveness of different acupuncture therapies for neck pain: A protocol for systematic review and/or network meta-analysis. Issue 16 (23rd April 2021) - Jo, Hyo-Rim; Noh, Eun-Ji; Oh, Se-Hee; Choi, Seong-Kyeong; Sung, Won-Suk; Choi, Su-Ji; Kim, Dong-Il; Hong, Seung-Ug; Kim, Eun-Jung
Abstract: Background: Neck pain is common musculoskeletal disorders in adult population. Acupuncture treatment has been widely used for treating neck pain. Nevertheless, previous systematic reviews (SRs) on acupuncture for neck pain remain controversial, and there is no SR for the comparative efficacy and safety of various types of acupuncture. Therefore, this study aims to evaluate and rank the effectiveness and safety of different types of acupuncture for neck pain by SR and network meta-analysis. Methods: Nine databases will be searched, including Ovid-MEDLINE, EMBASE, Cochrane library, China National Knowledge Infrastructure (CNKI), KoreaMed, Korean medical database (KMBASE), Korean Studies Information Service System (KISS), ScienceON, and Oriental Medicine Advanced Searching Integrated System (OASIS) from their inception to July 2021. The primary outcome is the change of pain intensity. A frequentist network meta-analysis will be performed to compare all relative outcomes of different acupuncture methods, using R software. The quality of included randomized controlled trials will be assessed by Cochrane Collaboration "risk of bias" tools and the evidence will be evaluated by the Grading of Recommendations Assessment, Development and Evaluation instrument. Results: The final findings of this network meta-analysis will be published in a recognized journal. Conclusions: Our study will evaluate and compare the effectiveness of various types of acupuncture for neck pain and provide clinicians with best option for what types of acupuncture treatments are effective. Trial registration number: INPLASY202120041